Exploration and evaluation of CAD modeling in virtual reality. Issue 6 (2nd November 2018) - Feeman, Seth M.; Wright, Landon B.; Salmon, John L.
ABSTRACT: Virtual reality (VR) technology has experienced a recent surge in popularity over the past few years and is finding more applications beyond entertainment. Three dimensional modeling is an application in which integration with VR technology is still in the development stage. The focus of this research is to evaluate the feasibility for computer-aided design in VR and to identify the best set of features for virtual reality modeling and practices in this new domain. A platform for testing CAD in VR is developed through the integration of CAD software with a game engine and compared against traditional CAD methods through testing. Modeling capabilities included previews, creating solid rectangular prisms and spheres, lock to grid, and cuts of similar shapes. User testing with four different models (i.e. chair, maze, truck, sculpture) and survey responses suggest respectively that design in virtual reality promoted greater creativity in modeling, allowed for a greater feature creation rate, and that a slight majority of test participants preferred modeling in VR compared to traditional CAD applications. GRAPHICAL ABSTRACT: